Underlying Perceptual Issues in Virtual Reality Systems: Does Display Type Affect Self-Motion Perception? - Riecke, B. E; Jordan, Jacqueline D.; Prpa, Mirjana; Feuereissen, Daniel (55th Annual Meeting of the Psychonomic Society (Psychonomics), 2014)
An embodied illusion of self-movement (vection) is a sensation necessary for allowing a convincing experience of self-motion in Virtual Reality (VR) when actual observer motion is unfeasible. While much research effort has been devoted to investigating how different stimulus parameters affect vection, there is little research investigating potential effects of the display itself. Using an active navigation task, we investigated if a stereoscopic projection system and a 3D TV would be similarly effective in inducing linear and curvilinear vection-in-depth in stationary observers if the field of view was matched. Repeated-measures ANOVAs revealed no significant difference between displays in neither vection onset latency, vection intensity, immersion, motion sickness, nor overall display preference. As expected, curvilinear paths yielded stronger vection with earlier vection onsets than straight paths. These results suggest that reported vection and user experience is surprisingly tolerant to display type. Further investigations that isolate individual display factors, such as luminance, contrast, resolution, or absolute size will provide a deeper understanding of their relative contribution and potential interactions.
Keywords: Riecke; Riecke_2014; bernhard-riecke; daniel-feuereissen; iat802; iat802_fall2013; jacqueline-jordan; mirjana-prpa; talkWithoutPaper; vection